La bailoterapia como estrategia de la alfabetización física en la mejora de la calidad de vida en personas adultas jóvenes - Ovaco Cun, Luis Fernando; Vivanco Castro, Scarlet Kaminski (Machala: Universidad Técnica de Machala, 2025)
This document presents a research study titled "Dance Therapy as a Physical Literacy Strategy to Improve Quality of Life," conducted by Ovaco Cun Luis Fernando and Vivanco Castro Scarlet Kaminski at the Technical University of Machala. The research addresses the issue of sedentary lifestyle and lack of physical literacy among young adults, specifically women aged 20 to 60 from the "16 de noviembre" neighborhood in the parish of La Iberia, province of El Oro. The overall objective was to analyze dance therapy as a physical literacy strategy to improve their quality of life. A mixed-method approach was used, with a descriptive and analytical type of research and a field design. The study population consisted of 40 women from the Blak Functional functional training group. Data were collected through structured interviews and the application of the EXERNET (quality of life) test and a physical literacy test. The findings revealed that dance therapy is an effective and viable strategy for promoting physical literacy and overall well-being. It combines exercise and dance, enhancing motivation, confidence, and physical competence, and contributes to physical, mental, emotional, and social well-being, including stress reduction and strengthening of community ties. Regular practice leads to positive changes in quality of life by improving body awareness and social interactions. As an integrative proposal, an exercise guide was developed for a structured dance therapy program organized into progressive guides, whose technical, economic, social, and environmental viability was confirmed.
Este documento presenta una investigación titulada "La bailoterapia como estrategia de la alfabetización física para la mejora de la calidad de vida", realizada por Ovaco Cun Luis Fernando y Vivanco Castro Scarlet Kaminski en la Universidad Técnica de Machala. La investigación aborda el problema del sedentarismo y la falta de alfabetización física en adultos jóvenes, específicamente en mujeres de 20 a 60 años del barrio "16 de noviembre" en la parroquia La Iberia, provincia de El Oro. El objetivo general fue analizar la bailoterapia como estrategia de alfabetización física para mejorar su calidad de vida. Se empleó un enfoque de investigación mixto, de tipo descriptivo y analítico, con un diseño de campo. La población de estudio consistió en 40 mujeres del grupo de entrenamiento funcional Blak Functional. Los datos se recopilaron mediante entrevistas estructuradas y la aplicación del test EXERNET (calidad de vida) y un test de alfabetización física1. Los hallazgos revelaron que la bailoterapia es una estrategia efectiva y viable para la alfabetización física y el bienestar integral. Combina ejercicio y baile, potenciando la motivación, confianza y competencia física, y contribuye al bienestar físico, mental, emocional y social, incluyendo la reducción del estrés y el fortalecimiento de lazos comunitarios. La práctica regular induce cambios positivos en la calidad de vida, mejorando la conciencia corporal y las interacciones sociales. Como propuesta integradora, se elaboró una guía de ejercicios para un programa de bailoterapia estructurada en guías progresivas, cuya viabilidad técnica, económica, social y ambiental fue confirmada.
Keywords: BAILOTERAPIA; ALFABETIZACIÓN FÍSICA; CALIDAD DE VIDA; ACTIVIDAD FÍSICA; RECREACIÓN